Development and evaluation of time‐resolved fluorescent immunochromatographic assay for quantitative detection of SARS‐CoV‐2 spike antigen. Issue 7 (12th June 2022) - Xu, Buzhou; Tang, Hao; Weng, Yiming; Jones, Valerie Sloane; Luo, Shuhong; Cho, Chih Yun; Lin, Yongping; Fang, Jianmin; Song, Xuedong; Huang, Ruo‐Pan
Abstract: Background: The spread of COVID‐19 worldwide caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has necessitated efficient, sensitive diagnostic methods to identify infected people. We report on the development of a rapid 15‐minute time‐resolved fluorescent (TRF) lateral flow immunochromatographic assay for the quantitative detection of the SARS‐CoV‐2 spike protein receptor‐binding domain (S1‐RBD). Objectives: Our objective was to develop an efficient method of detecting SARS‐CoV‐2 within 15 min of sample collection. Methods: We constructed and evaluated a portable, disposable lateral flow device, which detected the S1‐RBD protein directly in nasopharyngeal swab samples. The device emits a fluorescent signal in the presence of S1‐RBD, which can be captured by an automated TRF instrument. Results: The TRF lateral flow assay signal was linear from 0 to 20 ng/ml and demonstrated high accuracy and reproducibility. When evaluated with clinical nasopharyngeal swabs, the assay was performed at >80% sensitivity, >84% specificity, and > 82% accuracy for detection of the S1‐RBD antigen. Conclusion: The new S1‐RBD antigen test is a rapid (15 min), sensitive, and specific assay that requires minimal sample preparation. Critically, the assay correlated closely with PCR‐based methodology in nasopharyngeal swab samples, showing that the detected S1‐RBD antigen levels correlate with SARS‐CoV‐2 virus load. Therefore, the new TRF lateral flow test for S1‐RBD has potential application in point‐of‐care settings. Abstract : We have developed a portable, disposable, and quantitative lateral flow device, which detects the SARS‐CoV‐2 Spike antigen in 15 min using time‐resolved fluorescence. Compared with RT‐PCR, this assay has a sensitivity of 80.3% and a specificity of 83.64% in a cohort of 293 patients.